Study on sea sand as a partial replacement for fine aggregate - SIDHARDHAN, S.; SHEELA, S.JANSI; S MEYLIN, JESUS (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Sand researches around the world are in continuous search for the alternatives of sand. Fine aggregate is an important constituent of concrete and is required in large quantities. Generally, river sand is used as fine aggregate. Due to the increase in the utilization of concrete in construction sector, the need for river sand has been increased enormously. Hence, the abundant sea sand can be used as an alternative of river sand partially.The sea sand samples before (samples A and C) and after mineral extraction were utilized to replace for fine aggregate. The mineral extracted chiefly includes ilmenite, zircon, rutile, sillimanite and super garnet was confirmed by an analytical technique Energy-dispersive X-ray analysis (EDXA). Physical properties of these sands were recorded. Results reveal that the angle of internal friction (Ã˜) was high and low in sample A and C, but an opposite trend was observed for specific gravity.Â Except sample D, remaining samples belong to grade II size.Â Â Concrete cubes were laid for M35 grade concrete with the combinations of the above samples. The fine aggregate proportion from the design mix was replaced partially by 20% of sea sand. Compressive strength test and pull out test and the behaviour of concrete were conducted on the various soil specimens and the results were tabulated. The strength tests were conducted at 7, 14 and 28 days of water curing. Compressed strength, band strength as well the weight kg-1of the concrete did not affected by replacement of either sample A (10%) or sample B (20%). Proposed replacement is economically cheaper. Considering laboratory studied, we recommended to utilized sea sand for partial replacement for fine aggregate.Â